Understanding Corporate Life-Cycles - Ousanee Sawagvudcharee; Maurice Yolles; Gerhard Fink; Paul Iles; Chanchai Bunchapattanasakda; Buncha Limpabandhu (Journal of Education and Vocational Research, 2018)
This paper considers the nature of the dominant corporate paradigm, its change, failures or successes, and its relationship with the homeostatic organization. There is a popular way of understanding the dynamics of organizational change and that is through the pre-configured sequence of stages in a corporate life-cycle. Through there are a number of competing models for this kind of analysis. In all of them, the sequence of stages is defined by that which configures the life-cycle deterministically. However, there is little discussion given for how these models of organizations shift between stages, and none appear to dominate in the literature. A major criticism of these models is that they do not represent complex organizational processes of change. Therefore, this paper represents an alternative model, called â€œthe paradigm life-cycleâ€, which is connected to the homeostatic processes that maintain an organization, and which is, in principle, capable of generating corporate life-cycles under conditions of complexity.